2013
DOI: 10.1590/s1413-35552012005000117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of outpatient physical therapy intervention on pelvic floor muscles in women with urinary incontinence

Abstract: | Objective: To assess the effect of a weekly, short-term physical therapy intervention on the pelvic floor muscles and urinary incontinence (UI) among patients of the public health system. Method: Quasi-experimental before-and-after study. Clinical history and function evaluation were performed using perineal bidigital maneuvers and perineometry. The intervention consisted of transvaginal electrical stimulation and pelvic floor kinesiotherapy. Data were analyzed using the paired t test or Wilcoxon signed-rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
7
0
3
Order By: Relevance
“…This finding corroborates the results of previous studies 5,13 and may be related to the fact that MS patients may present with both detrusor muscle abnormality (urgency symptoms and vesical hyperactivity) and sphincter disorders (stress-related symptoms) 12,14 . In addition, the studied sample seems to be susceptible to risk factors related to MUI, such as vaginal delivery, more than one pregnancy, and menopause, which may also explain the prevalence of MUI in this sample and corroborates findings from other studies in which MUI was also more prevalent in samples susceptible to these risk factors 15 .…”
Section: Discussionsupporting
confidence: 89%
“…This finding corroborates the results of previous studies 5,13 and may be related to the fact that MS patients may present with both detrusor muscle abnormality (urgency symptoms and vesical hyperactivity) and sphincter disorders (stress-related symptoms) 12,14 . In addition, the studied sample seems to be susceptible to risk factors related to MUI, such as vaginal delivery, more than one pregnancy, and menopause, which may also explain the prevalence of MUI in this sample and corroborates findings from other studies in which MUI was also more prevalent in samples susceptible to these risk factors 15 .…”
Section: Discussionsupporting
confidence: 89%
“…The higher prevalence of UUI and mixed UI in the elderly women of this study confirms the findings of other authors 12,13,22,23 . The elderly women reported having lived with urine leakage for a median of three years, which corroborates the findings of other studies on women, particularly elderly, that state that these individuals live with UI for long periods of time before seeking help 20,21,24,25 . Even more concerning is the fact that 25% of them had been living with UI for 7.7 years or longer without seeking help (Table 2).…”
supporting
confidence: 87%
“…As seen in the literature, physical therapy is efficient in reducing urine loss and improving pelvic floor muscle function and QOL. It can be easily carried out in Primary Health Care Units at low costs 5,17,19,24 , either in groups or individually (in the latter case, after approximately 14 treatment sessions 24 ). Taking into consideration the effectiveness of the physical therapy treatment reported in the literature 19,24 , the high prevalence of UI found among the elderly women in this sample, the connection between UI, functional decline 30 and falls in the elderly 32 and the subsequent loss of independence that affects most of the fallers 33 , it is suggested that the elderly users of the public health system should be given access to this therapeutic modality.…”
mentioning
confidence: 99%
“…Worldwide, it is estimated that 25‐45% of women suffer from this condition. UI may lower quality of life as it affects social, emotional, and psychological aspects of life . Treatment for UI should be multidisciplinary and based on two pillars: medical treatment and Physical Therapy (PT) .…”
Section: Introductionmentioning
confidence: 99%
“…UI may lower quality of life as it affects social, emotional, and psychological aspects of life. 2 Treatment for UI should be multidisciplinary and based on two pillars: medical treatment and Physical Therapy (PT). 3 PT is considered the first-line treatment for this condition and should be tried before medication or surgery.…”
Section: Introductionmentioning
confidence: 99%